The impact of partial vascular occlusion on oxidative stress markers during resistance exercise - Garten, R. S.; Goldfarb, A.; Crabb, B.; Waller, J. (International Journal of Sports Medicine, 2015)
This study sought to examine the effects of partial vascular occlusion (PVO) on oxidative stress markers in response to resistance exercise and at rest in young resistance-trained males. 12 resistance-trained males performed 6 conditions in random counterbalanced order: rest (R), low-intensity (LIRE: 30% 1RM) and moderate-intensity (MIRE: 70% 1RM) resistance exercise with or without PVO. Blood samples were obtained before and immediately after each condition and plasma protein carbonyls (PC), glutathione ratio, oxygen radical absorbance capacity (ORAC), and xanthine oxidase (XO) were evaluated. The addition of PVO resulted in significantly greater plasma PC and glutathione ratio in the rest condition. During LIRE the addition of PVO significantly attenuated plasma PC. The MIRE condition, independent of PVO, resulted in significantly higher PC concentration and glutathione ratio compared to the rest and LIRE conditions. The addition of PVO during MIRE resulted in a significant increase in PC. Thus, this study revealed that PVO increased oxidative stress at rest and enhanced the oxidative stress response to MIRE, but when combined with LIRE oxidative stress was attenuated. These findings suggest that the utilization of PVO during LIRE may alter ROS-induced accumulation in the blood which may influence cellular signaling.